2012
DOI: 10.1002/chem.201103791
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Cleavage of Cyclobutane Rings in Photodimerized Coordination‐Polymeric Sheets

Abstract: Three coordination polymers, [Cd(2)(pvba)(2)(tbdc)(dmf)(2)] (1), [Co(2)(pvba)(2)(tbdc)(dmf)(2)(H(2)O)(2)] (2), and [Ni(2)(pvba)(2)(tbdc)(dmf)(2)(H(2)O)(2)] (3) (H(2)tbdc = 2,3,5,6-tetrabromobenzenedicarboxylic acid, Hpvba = trans-2-(4'-pyridyl)vinylbenzoic acid), were synthesized by solvothermal methods. The solid-state structures of compounds 1 and 2 were determined by X-ray crystallography. In compounds 1 and 2, the bimetallic cores acted as secondary building units that connected the tbdc ligands in one dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
5
1
1

Relationship

6
1

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 103 publications
1
37
0
1
Order By: Relevance
“…Telfer has pioneered thermolytic post-synthetic deprotection (PSD) chemistry through the instability of tert-butoxycarbamates to unveil amine groups in MOFs, with the additional benefit of concomitant pore enlargement. 7 Very recently, Vittal 8 found that direct heating could dismember cyclobutane rings via a reverse [2 + 2] cycloaddition process. We sought to explore thermal post-synthetic rearrangement (PSR) chemistry in MOFs as a simple and efficient way of bringing out new functionality in these materials.…”
mentioning
confidence: 99%
“…Telfer has pioneered thermolytic post-synthetic deprotection (PSD) chemistry through the instability of tert-butoxycarbamates to unveil amine groups in MOFs, with the additional benefit of concomitant pore enlargement. 7 Very recently, Vittal 8 found that direct heating could dismember cyclobutane rings via a reverse [2 + 2] cycloaddition process. We sought to explore thermal post-synthetic rearrangement (PSR) chemistry in MOFs as a simple and efficient way of bringing out new functionality in these materials.…”
mentioning
confidence: 99%
“…This property was investigated in a 2D CP by thermal treatment. 52 The asymmetric ligand, trans-2-(4 ′ -pyridyl)vinylbenzoic acid (Hpvba) forms the following three photoreactive 2D CPs: [Cd 2 (pvba) 2 where tbdc = 2,3,5,6-tetra-bromobenzene dicarboxylate. In the sheet structure, [Cd 2 (O 2 C-C) 4 (pyridyl) 2 ] core is the repeating unit connecting a pair of pvba ligands that are aligned parallel in an HT manner, whereas the tbdc ligands are arranged in the orthogonal direction.…”
Section: Thermal Cyclo-reversion Of Photoreacted 2d Cpsmentioning
confidence: 99%
“…This photochemical reaction has been accompanied by a solid-state structural transformation between two different sheet structures as shown in Figure 20. 52 Further, the cyclobutane rings in the photodimerized product of 32 can be cleaved by heating to 220 ∘ C for 12 h under vacuum in two different ways to yield a mixture of trans-and cis-isomers of pvba quantitatively as monitored by the 1 H-NMR spectroscopy. This transformation as depicted in Figure 20 appears to be the first attempt to reverse the cyclized product in CPs.…”
Section: Thermal Cyclo-reversion Of Photoreacted 2d Cpsmentioning
confidence: 99%
“…However, such cleavage of cyclobutane rings in CPs has never been observed. Recently, Vittal's laboratory has succeeded in cleaving the cyclobutane rings once formed in a 2D CP by thermal treatment [48]. The following photo-reactive 2D CPs have been synthesized using an asymmetric ligand, trans- 4 (pyridyl) 2 ] core is the repeating unit connecting a pair of pvba ligands which are aligned in head-to-tail parallel fashion in the orthogonal direction and the tbdc ligands in the perpendicular direction.…”
Section: D To 2dmentioning
confidence: 99%
“…This photochemical reaction has been accompanied by a solid-state structural transformation from one 2D structure to another as shown in Fig. 20 [48].…”
Section: D To 2dmentioning
confidence: 99%